INTEGRATING HOTS USING SPIDER WEB MULTIPLICATION IN BASIC MULTIPLICATION FACTS - Marion, Zuraini Binti (PEOPLE: International Journal of Social Sciences, 2020)
The traditional methods are commonly practiced in the learning of basic multiplication facts in schools. These kinds of learning usually emphasizing on memorization and repetition. These methods do not encourage pupils' to think and do not improve their thinking skills. This action research was conducted to study whether the integration of HOTS by using Spider Web Multiplication model improve the primary school basic multiplication facts ability among the School In Hospital (SIH) pupils in Sultanah Fatimah Specialist Hospital in Muar, Johor, Malaysia. The study is also carried out to study whether the integration of HOTS in the model improve the pupils’ interest and motivation to learn basic multiplication facts. Five pupils ranging from lower to upper primary pupils are selected randomly. The pre and post-test were used to determine the pupils’ skill in basic multiplication facts. Meanwhile observations were carried out to gather information of the learning process. Furthermore informal interviews were carried out to know the pupils’ interest and motivation in learning basic multiplication facts after the learning sessions. The result of the pre and the post test revealed that the pupils’ ability in basics multiplication facts improved after the learning session. The observations showed that the integration of HOTS in the learning activities involving analyzing, designing, combining, identifying and creating in the learning process help the pupils a lot in the learning of basic multiplication facts. The pupils’ interest and motivation in learning basic multiplication facts also improved. Based on the findings, the integration of HOTS which was used in Spider Web Multiplication is recommended in teaching of basic mathematical facts.